Illness among paralympic athletes: Epidemiology, risk markers, and preventative strategies - Van Rensburg, D. C. J.; Schwellnus, M.; Derman, W.; Webborn, N. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Paralympic athletes have unique preexisting medical conditions that predispose them to increased risk of illness, but data are limited to studies conducted during the last 3 Paralympic Games. This article reviews the epidemiology of illness (risk, patterns, and predictors) in Paralympic athletes and provides practical guidelines for illness prevention. The incidence rate of illness (per 1000 athlete-days) in Paralympic athletes is high in Summer (10.0-13.2) and Winter (18.7) Paralympic Games. The authors propose general and specific guidelines on preventative strategies regarding illness in these athletes.